Characterization of electron density of states in laser-superposed channeling regime. (10th October 2014) - Berec, Vesna
Abstract: We present low-dimensional functionalization and characterization of electron density of states using highly correlated/precisely guided proton beam trajectories and a silicon nanocrystal as a target, representing at a same time a versatile nanolaser technique capable for coherent control of atomic quantum states and for scanning the interior of an atom with resolution comparable to 10% of the Bohr radius.